Imagining an ideal husband: Marriage as a site of aspiration among pious Somali women in London - Liberatore, G (George Washington University, Institute for Ethnographic Research, 2015)
This article is about “marriage talk” and the forms of imagination and aspiration that it entails. It draws on discussions and debates about ideal husbands among young Somali Muslim women in Britain who, in recent years, have begun practising Islam. Through these debates, these women draw on various different discourses, values, norms and ideals to re-think and re-imagine themselves in relation to multiple others, including kin, friends and God. Marriage, I argue, is a site of aspiration (Khan 2012), as it engages the ethical imagination—the means and modes by which individuals re-imagine relations to self and others (Moore 2011). By reflecting on, discussing and imagining a future spouse, these young women draw on different forms of knowledge in relation to enlarged visions of self and other. I demonstrate that analyses of the complexly constituted Muslim subject (Schielke 2010a, Deeb and Harb 2013) need to pay attention not only to the coexistence of multiple moral registers or rubrics, but also to how these connect to the ways in which individuals imagine new ways of being. The article brings to the fore the importance of intersubjectivity and shines light on the processes of imagining and aspiring, which are crucial for an understanding of the complex lives of young women who turn to practise Islam.